Microfluidic-Assisted Synthesis of Metal—Organic Framework —Alginate Micro-Particles for Sustained Drug Delivery - Akhilesh Bendre; Vinayak Hegde; Kanalli V. Ajeya; Subrahmanya Thagare Manjunatha; Derangula Somasekhara; Varalakshmi K. Nadumane; Krishna Kant; Ho-Young Jung; Wei-Song Hung; Mahaveer D. Kurkuri (Biosensors, 2023)
Drug delivery systems (DDS) are continuously being explored since humans are facing more numerous complicated diseases than ever before. These systems can preserve the drug’s functionality and improve its efficacy until the drug is delivered to a specific site within the body. One of the least used materials for this purpose are metal—organic frameworks (MOFs). MOFs possess many properties, including their high surface area and the possibility for the addition of functional surface moieties, that make them ideal drug delivery vehicles. Such properties can be further improved by combining different materials (such as metals or ligands) and utilizing various synthesis techniques. In this work, the microfluidic technique is used to synthesize Zeolitic Imidazole Framework-67 (ZIF-67) containing cobalt ions as well as its bimetallic variant with cobalt and zinc as ZnZIF-67 to be subsequently loaded with diclofenac sodium and incorporated into sodium alginate beads for sustained drug delivery. This study shows the utilization of a microfluidic approach to synthesize MOF variants. Furthermore, these MOFs were incorporated into a biopolymer (sodium alginate) to produce a reliable DDS which can perform sustained drug releases for up to 6 days (for 90% of the full amount released), whereas MOFs without the biopolymer showed sudden release within the first day.